Military rank and AIDS proportionate mortality in the Brazilian Navy Hierarquia militar e mortalidade proporcional por AIDS na Marinha do Brasil - Marlene Silva; Vilma Santana; Inês Dourado (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
This study describes AIDS mortality and occupational factors among servicemen in the Brazilian Navy. This is a proportional mortality study of 2,586 servicemen's death certificates (20-72 years of age) recorded from 1991 to 1995. Death certificates and occupational histories came from the Brazilian Navy Insurance System archives. Association was measured using proportionate mortality odds ratios obtained with unconditional logistic regression. AIDS proportionate mortality was estimated at 4.8% (n = 125) and increased during the study period, particularly among servicemen under 50 years of age and those with low rank. As compared to other occupations, there was relative excess AIDS in the "management" (proportionate mortality odds ratio, PMORage-adjusted = 2.45; 95%CI: 1.27-4.71), "secretarial" (PMORage-adjusted = 2.49; 95%CI: 1.22-5.08), and "janitorial" (PMORage-adjusted = 2.61; 95%CI: 1.10-6.16) occupational groups. AIDS proportionate mortality was higher among male than female military members. Higher rates were observed in some occupational groups when the members were low ranking. Power distribution, gender issues, and low socioeconomic status require further investigation using more appropriate methods. Este estudo descreve a mortalidade proporcional por AIDS associada aos fatores ocupacionais na Marinha do Brasil. Inclui 2.586 certidões de óbitos de militares entre 20 e 72 anos, ocorridos em 1991-1995. Os dados de certidões de óbitos e história ocupacional foram obtidos nos arquivos do Serviço de Inativos e Pensionistas da Marinha. Utiliza-se como medida de associação odds ratio de mortalidade proporcional obtida por regressão logística não condicional. Estimou-se uma mortalidade proporcional por AIDS de 4,8% (n = 125) que aumentou no período, particularmente, entre os menores de 50 anos ou de nível hierárquico baixo. Nesta categoria, encontrou-se excesso relativo na mortalidade proporcional por AIDS nos grupos ocupacionais de "Administração" (odds ratio de mortalidade proporcional, ORMPajustada = 2,45; IC95%: 1,27-4,71), "Secretaria" (ORMPajustada = 2,49; IC95%: 1,22-5,08), e "Taifeiros" (ORMPajustada = 2,61; IC95%: 1,10-6,16), comparados às demais ocupações. A mortalidade proporcional por AIDS esteve aumentada entre militares do sexo masculino, sendo elevada em algumas ocupações no nível hierárquico baixo. Todavia, distribuição de poder, questões de gênero e nível sócio-econômico necessitam de melhor investigação com desenhos apropriados.